2011
DOI: 10.1111/j.1751-7133.2010.00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Volume Measurements in Patients With Heart Failure and a Preserved Ejection Fraction: Implications for Diagnosing Anemia

Abstract: Racial differences in the prevalence of anemia in patients with heart failure have been noted. The diagnosis of anemia in heart failure patients can be confounded by many factors. Plasma volume expansion is one of the most prominent confounders. We will study the difference of anemia prevalence using two different diagnostic techniques: peripheral hemoglobin recommended by the World Health Organization (WHO criteria) and blood volume (BV) analysis. We will also compare racial disparities in the prevalence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
(57 reference statements)
0
16
0
8
Order By: Relevance
“…Patients with‘ pre-clinical’ HFpEF often have impaired natriuretic function [165], and even seemingly well compensated HFpEF patients often have elevated plasma volume [166]. Some view volume overload and congestion as key contributors to HF development and progression [167].…”
Section: Rv Dysfunction Pulmonary Vascular Disease and Other Hemodynmentioning
confidence: 99%
“…Patients with‘ pre-clinical’ HFpEF often have impaired natriuretic function [165], and even seemingly well compensated HFpEF patients often have elevated plasma volume [166]. Some view volume overload and congestion as key contributors to HF development and progression [167].…”
Section: Rv Dysfunction Pulmonary Vascular Disease and Other Hemodynmentioning
confidence: 99%
“…Extracellular water assessed using whole‐body bioelectrical impedance is also increased in patients with anemia 2 . As previously pointed out, this association appears throughout the spectrum of CHF, being also present in patients with preserved LV systolic function 1,2 . However, hemodilution may also be present in patients who appear to have euvolemia 12,25 …”
mentioning
confidence: 77%
“…Recent studies have demonstrated the relevance of extracellular volume measurement for the diagnosis of anemia in chronic heart failure both with systolic dysfunction and preserved left ventricular function 1,2 . However, the implications for treatment have not been comprehensively elucidated.…”
mentioning
confidence: 99%
“…Specimens will be analyzed with an automated system (BVA100 Blood Volume Analyzer, Daxor Corp., NY). 35 …”
Section: Methodsmentioning
confidence: 99%